2016
DOI: 10.1542/peds.2016-0445
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes Associated With Isolated Agenesis of the Corpus Callosum: A Meta-analysis

Abstract: CONTEXT: Antenatal counseling in cases of agenesis of the corpus callosum (ACC) is challenging. OBJECTIVES:To ascertain the outcome in fetuses with isolated complete ACC and partial ACC.DATA SOURCES: Medline, Embase, CINAHL, and Cochrane databases. STUDY SELECTION:Studies reporting a prenatal diagnosis of ACC. The outcomes observed were: chromosomal abnormalities at standard karyotype and chromosomal microarray (CMA) analysis, additional anomalies detected only at prenatal MRI and at postnatal imaging or clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
122
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(133 citation statements)
references
References 41 publications
2
122
1
1
Order By: Relevance
“…Analyses revealed that some risk factors were important predictors for specific aspects of neuropsychological functioning, even after Bonferroni correction (p<.006), (Bedeschi et al, 2006;D'Antonio et al, 2016;Moutard et al, 2003;Shevell, 2002;Siffredi et al, 2017). This study provides the first comprehensive report of general intellectual, academic, executive, behavioral and social functioning in a cohort of school-age children presenting for clinical services to a hospital and diagnosed with AgCC confirmed on MRI.…”
Section: Risk Factors Associated With Neuropsychological Functioningmentioning
confidence: 81%
“…Analyses revealed that some risk factors were important predictors for specific aspects of neuropsychological functioning, even after Bonferroni correction (p<.006), (Bedeschi et al, 2006;D'Antonio et al, 2016;Moutard et al, 2003;Shevell, 2002;Siffredi et al, 2017). This study provides the first comprehensive report of general intellectual, academic, executive, behavioral and social functioning in a cohort of school-age children presenting for clinical services to a hospital and diagnosed with AgCC confirmed on MRI.…”
Section: Risk Factors Associated With Neuropsychological Functioningmentioning
confidence: 81%
“…MRI is considered the gold standard for the diagnosis of ACC because of its superior sensitivity and ability to differentiate iACC and complex ACC (ACC with additional brain abnormalities) (Rapp et al., ; Tercanli & Prufer, ; Wright, Sibley, & Baker, ). The distinction of the latter is important in a prenatal setting as individuals with iACC generally have a favorable developmental outcome compared with those with complex ACC (D'Antonio et al., ; des Portes et al., ; Edwards, Sherr, Barkovich, & Richards, ; Sotiriadis & Makrydimas, ). Likewise, individuals with DCC ‐iACC have a favorable developmental outcome while individuals with DSBS have a poor developmental outcome.…”
Section: Diagnostic Strategiesmentioning
confidence: 99%
“…ACC is not indicative for seizure disorder, more often additional malformations of cortical development are causal. Microstructural CC abnormalities are detected by advanced imaging techniques and they constitute a part of diffuse white matter disturbance (12)(13)(14). In our study, there were 3 patients with ACC, two of them had epilepsy and all three of them were intellectually disabled.…”
Section: Discussionmentioning
confidence: 68%